2016
DOI: 10.1111/gcbb.12376
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar application on soil greenhouse gas fluxes: a meta‐analysis

Abstract: Biochar application to soils may increase carbon (C) sequestration due to the inputs of recalcitrant organic C. However, the effects of biochar application on the soil greenhouse gases (GHGs) fluxes appear variable among many case studies; therefore the efficacy of biochar as a carbon sequestration agent for climate change mitigation remains uncertain. We performed a meta-analysis of 91 published papers with 552 paired comparisons to obtain a central tendency of three main GHG fluxes (i.e., CO 2 , CH 4 , and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
201
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(216 citation statements)
references
References 94 publications
(154 reference statements)
11
201
4
Order By: Relevance
“…In general, fertilized biochar treatments expelled an elevated amount of CO 2 compared to their non-fertilized counterparts; however, the effect was not significantly proved. This study supports the findings of several scientists in terms of CO 2 emission from upland and paddy fields [13] [15]. They also revealed the fact that, lower biochar application rates (≤10 t·ha −1 ) decrease CO 2 emissions which comply with this experiment at the submerged condition.…”
Section: Effect On Co2 Emissionsupporting
confidence: 92%
See 2 more Smart Citations
“…In general, fertilized biochar treatments expelled an elevated amount of CO 2 compared to their non-fertilized counterparts; however, the effect was not significantly proved. This study supports the findings of several scientists in terms of CO 2 emission from upland and paddy fields [13] [15]. They also revealed the fact that, lower biochar application rates (≤10 t·ha −1 ) decrease CO 2 emissions which comply with this experiment at the submerged condition.…”
Section: Effect On Co2 Emissionsupporting
confidence: 92%
“…The only fertilized treatment became the principal emitter with 1748 kg·ha −1 followed by the control (1625 kg·ha −1 ). Similar trends of increased soil CO 2 fluxed immediately after flooding were seen by a group of scientist, exceeded pre-flooding values by two-thirds [13] [27]. This increase is unexpected and pulse like.…”
Section: Effect On Co2 Emissionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results of meta-analysis conducted by He et al [47] also showed that biochar application significantly increased soil CO 2 fluxes by 22.14%. They discussed that the stimulation of soil CO 2 fluxes might be associated with the higher soil organic C status and the more active soil microbial activities since biochar application enhanced soil organic C and soil microbial biomass C [48].…”
Section: Co 2 Emissionsmentioning
confidence: 88%
“…The air samples were collected on 0, 1, 2, 3,4,7,11,14,18,25,28,32,36,39,43,47,50,57,63,68,75, 83 and 90 days of incubation. Before sampling, the jars were thoroughly flushed with ambient air and left opened for approximately 30 min to equilibrate with the atmosphere [23].…”
Section: Gas Sampling and Analysismentioning
confidence: 99%